EXPLORING THE ROLE OF DEVELOPMENTAL GUIDANCE AND COUNSELLING IN THE MERDEKA CURRICULUM - Amalia, Riza; Lutfatulatifah; Rudi Haryadi (Jurusan Bimbingan dan Konseling, 2025)
This study aims to explore the implementation of developmental guidance and counseling within the context of the Merdeka Curriculum at the Senior High School level in Central Kalimantan Province. A qualitative case study approach was employed, involving three guidance and counseling teachers from different schools. Data collection was conducted through in-depth interviews, and the data were analyzed using the Miles and Huberman model. The findings highlight two key themes: (1) the implementation of developmental guidance and counseling programs, which include assessments of students’ learning styles, interest-based subject mapping, and support for higher education pathways, and (2) the challenges and constraints, such as limited teacher readiness, students' adaptation difficulties, and inadequate facilities. The study underscores the role of developmental guidance and counseling in fostering students’ personal and academic growth within the independent learning framework. The implications emphasize the need for enhanced governmental support, stronger school-community collaboration, and more structured counseling hours within the curriculum. The novelty of this research lies in its focus on the practical application of developmental guidance and counseling within the Merdeka Curriculum, contributing insights into optimizing its implementation in Indonesian schools. Keywords: Developmental guidance and counselling, Merdeka Curriculum, High School